Concomitance and interactions of pathogens in the Iberian wolf (Canis lupus). (August 2015) - Oleaga, A.; Vicente, J.; Ferroglio, E.; Pegoraro de Macedo, M.R.; Casais, R.; del Cerro, A.; Espí, A.; García, E.J.; Gortázar, C.
Abstract: With the aim of improving our understanding of their epidemiological features, exposure to or presence of Canine Parvovirus (CPV), Canine Distemper Virus (CDV), Leishmania infantum and Sarcoptes scabiei were studied in 88 wild wolves from Asturias (Northern Spain) by means of long-term (2004–2010) serological and molecular data. Individual and population factors and the possible interactions between them were also statistically analyzed for better understanding the contact/presence of studied pathogens. The overall seroprevalence values were 19%, 61%, 20% and 0% for CDV, CPV, S. scabiei and Leishmania, respectively, while a 46% of studied wolves showed Leishmania genetic material presence. Sarcoptic mange, CDV and CPV showed higher seroprevalence values in the areas with higher wolf densities, and a positive association between CDV and S. scabiei antibody responses was detected. Reported data highlight the need of considering concomitant pathogens and their possible interactions for a better understanding of diseases and their management in wildlife. Highlights: We studied the exposure/presence of four pathogens in Iberian wolves during 7 years. Seroprevalence for both sarcoptic mange and Canine Distemper Virus was close to 20%. Canine Parvovirus (61% seroprevalence) can be considered endemic in Asturian wolves. A striking 46% of studied wolves showed Leishmania genetic material presence. A positive association between CDV and S. scabiei antibody responses was detected.